Assessment of Risk Factors for Non-communicable Diseases among Young Adults in Kerala, India - Ahana Salam; Jayakrishnan Thayyil; Nithya Girija; Anjali Lakshmanan; Sruthikrishna Punathukandi; Anupama Raj Karattuthazhathu (Preventive Medicine: Research & Reviews)
Objectives: To estimate risk factors for non-communicable diseases (NCDs) amongst young adults and to determine the association between NCDs and various risk factors amongst young adults. Materials and Methods: This study was done amongst 150 young adults of Kerala. The data were collected by conducting direct interviews with the use of pre-designed semi-structured questionnaire. Anthropometric and biochemical parameters such as total cholesterol, low-density lipids were collected and analysed using standard methods. Results: Amongst the 150 study participants, 104 (69.4%) were girls and 46 (30.6%) were boys. Amongst these 68 (45.3%) had body mass index (BMI) >23. The study shows that 25.3% and 27.3% of participants had high diastolic blood pressure (DBP) and systolic blood pressure (SBP), respectively. Males had high BP, whereas abdominal adiposity was more amongst females. Physical activity amongst participants was very low. There is a positive correlation between BMI and SBP (r = 0.28, odds ratio [OR] =3.9); BMI and DBP (r = 0.24, OR = 2.9) and waist circumference (WC) with SBP (r = 0.25,); WC and DBP (r = 0.283). The increased BMI (crude odds ratio-3.979; 95% confidence interval-1.490–10.625) has got association with hypertension. Conclusions: There is a high prevalence of risk factors of NCDs amongst the young adult population of Kerala. The findings emphasise the need for interventions to reduce these risk factors amongst these young adults by life cycle approach.